2000
DOI: 10.1007/s002210050003
|View full text |Cite
|
Sign up to set email alerts
|

Activity of respiratory laryngeal motoneurons during fictive coughing and swallowing

Abstract: Membrane potential changes and discharges from 28 laryngeal motoneurons were recorded intracellularly in the caudal nucleus ambiguus of decerebrate, paralyzed and ventilated cats. Electrical activities were recorded from 17 expiratory laryngeal motoneurons (ELMs) with maximal depolarizing membrane potential in early expiration, and from 11 inspiratory laryngeal motoneurons (ILMs) with maximal depolarizing membrane potential in inspiration. Activities during breathing were compared with those observed during fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
69
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 35 publications
13
69
2
Order By: Relevance
“…Furthermore, the laryngeal motor pattern during cough can be variable in the same as well as in different experimental preparations (2,16,34,37,43). These observations support the concept that cranial and spinal motor outputs are subject to different regulation specifically during cough (36,43).…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, the laryngeal motor pattern during cough can be variable in the same as well as in different experimental preparations (2,16,34,37,43). These observations support the concept that cranial and spinal motor outputs are subject to different regulation specifically during cough (36,43).…”
Section: Discussionsupporting
confidence: 67%
“…ELMs are inhibited at the initiation of swallowing, as shown in (Shiba et al, 1999;Gestreau et al, 2000). The present study showed that BÖ T/preBÖ T EAUG neurons having inhibitory monosynaptic connections with ELMs are suppressed during swallowing.…”
Section: Discussionsupporting
confidence: 66%
“…In contrast to these behaviors, EAUG neurons were silent during the swallow-related hyperpolarization of ELMs. The swallow-related inhibition preceding excitation in adductor motoneurons (Gestreau et al, 2000) is important for temporal organization of the swallowing motor sequence (Zoungrana et al, 1997). However, the laryngeal motor pattern of swallowing did not use EAUG inhibitory neurons as an inhibitory synaptic source, although the silence of EAUG neurons might indirectly contribute to the swallow-related excitation of ELMs.…”
Section: Discussionmentioning
confidence: 97%
“…However, it is known that rhythmic swallow can alternate between repetitive laryngeal coughs (Gestreau et al, 2000). This observation indicates that the system will allow alternating expression of two rhythmic nonbreathing behaviors.…”
Section: The Holarchical System and The Expression Of Multiple Behaviorsmentioning
confidence: 99%
“…To be sure, there must be significant temporal correlation between the two behaviors for each to be executed in an appropriate fashion. Indeed, in an example shown in one study (Gestreau et al, 2000) swallows were initiated and completed in the cough expiratory interval. This overlapping expression of two rhythmic behaviors is entirely consistent with the concept that the oscillators for swallow and cough are functionally separate (Jean, 2001;Saito et al, 2003).…”
Section: The Holarchical System and The Expression Of Multiple Behaviorsmentioning
confidence: 99%